Cultural Dance Program Improves Hypertension Management for Native Hawaiians and Pacific Islanders: a Pilot Randomized Trial - Kaholokula, Joseph Keawe‘aimoku (J Racial Ethn Health Disparities, 2015)
OBJECTIVE: Native Hawaiians and Pacific Islanders (NHPI) bear an unequal burden of hypertension and cardiovascular disease. Hula, the traditional dance of Hawaii, has shown to be a culturally meaningful form of moderate-vigorous physical activity for NHPI. A pilot study was done in Honolulu, Hawaii, to test a 12-week hula-based intervention, coupled with self-care education, on blood pressure management in NHPI with hypertension in 2013. METHOD: NHPI with a systolic blood pressure (SBP) ≥140 mmHg were randomized to the intervention (n = 27) or a wait-list control (n = 28). Blood pressure, physical functioning, and eight aspects of health-related quality of life (HRQL) were assessed. RESULTS: The intervention resulted in a reduction in SBP compared to control (−18.3 vs. −7.6 mmHg, respectively, p ≤ 0.05) from baseline to 3-month post-intervention. Improvements in HRQL measures of bodily pain and social functioning were significantly associated with SBP improvements in both groups. CONCLUSION: Using hula as the physical activity component of a hypertension intervention can serve as a culturally congruent strategy to blood pressure management in NHPI with hypertension. TRIAL REGISTRATION: clinicaltrials.gov Identifier: NCT01995812